Exact solutions of the Kudryashov–Sinelshchikov equation and nonlinear telegraph equation via the first integral method - Mirzazadeh, Mohammad; Eslami, Mostafa (Nonlinear Analysis: Modelling and Control, 2012)
In this article we find the exact traveling wave solutions of the Kudryashov–Sinelshchikov equation and nonlinear telegraph equation by using the first integral method. This method is based on the theory of commutative algebra. This method can be applied to nonintegrable equations as well as to integrable ones.